2014
DOI: 10.1080/19440049.2014.991948
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of ochratoxin A byBacillus amyloliquefaciensASAG1

Abstract: Ochratoxin A (OTA) is widely found in food and feed products as a mycotoxin contaminant. It is produced by Penicillium species and several Aspergillus species. The identification OTA detoxification microorganisms is believed to be the best approach for decontamination. In this study, we isolated ASAG1, a bacterium with the ability to degrade OTA effectively, from grain depot-stored maize. A 16S rDNA sequencing approach was used to identify this strain as Bacillus amyloliquefaciens ASAG1. The degradation of OTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 23 publications
1
62
0
Order By: Relevance
“…A careful selection of environmental sources more likely to harbor MBMs should increase the probability of finding functional microorganisms. Previous studies have isolated microorganisms from a range of environmental [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], plant [30,31,32,33,34,35,36,37,38] and animal [39,40,41,42,43,44,45,46,47,48] sources.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A careful selection of environmental sources more likely to harbor MBMs should increase the probability of finding functional microorganisms. Previous studies have isolated microorganisms from a range of environmental [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29], plant [30,31,32,33,34,35,36,37,38] and animal [39,40,41,42,43,44,45,46,47,48] sources.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…These may include light [18,54], phase contrast, bright field [59] and electron microscopy [12,16,57] to determine cell size, shape and Gram-stain type. Biochemical tests, such as carbon source utilization, enzyme activity and chemical sensitivities [18,19,27,33,38,45,46,50,58,59,81], as well as commercial identification systems, such as BIOLOG or API ® strips, may also be used for the identification of MBMs [12,21,35,60]. In addition, fatty acid and ribosomal protein profiles may be determined using gas chromatographic analysis of fatty acid methyl esters (GC-FAME) and matrix assisted laser desorption/ionization-time of flight (MALDI-TOF) techniques, respectively [12,59].…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…In addition, Shi et al (2014) reported the degradation of 97% of DTA levels using a cell-free supernatant from one strain of B. subtilis and its ability to inhibit mycelial growth by 33% of another Aspergillus section Circumdati, A. ochraceus, which is a close related to A. westerdijkiae's (Visagie et al, 2014). DTA degradation was also reported by Chang et al (2015), which observed mycotoxin degradation using cells and cell-free metabolites of one strain of B. amyloliquefaciens. Dur findings and those reported by Petchkongkaew et al (2008) confirm the potential biotechnological applications of these bacteria on reducing DTA production by A. westerdijkiae and its growth on coffee beans.…”
Section: Resultsmentioning
confidence: 86%
“…Among them, six genes code for peptidases and resulted up-regulated at 6 h ( Table 2 ). PJ15_1540 and PJ15_2908 both code for a serine-type D-Ala-D-Ala carboxypeptidase similar to the ASAG1 carboxypeptidase of Bacillus amyloliquefaciens , which was reported to degrade OTA in vitro (Chang et al, 2015). PJ15_1540 was selected for the experimental validation based on its higher identity (29%) with the ASAG1 carboxypeptidase.…”
Section: Resultsmentioning
confidence: 99%
“…The strongest candidates were PJ15_1540 and PJ15_2908, coding for two serine-type D-Ala-D-Ala carboxypeptidases showing 33% of sequence identity. Indeed, PJ15_1540 and PJ15_2908 proteins showed 29 and 25 identity, respectively, with ASAG1 carboxypeptidase of B. amyloliquefaciens , which was reported to degrade OTA in vitro (Chang et al, 2015). …”
Section: Discussionmentioning
confidence: 99%